PENGARUH PRAKTIK KERJA INDUSTRI DAN FASILITAS BELAJAR TERHADAP KESIAPAN KERJA PESERTA DIDIK DI SMK KABUPATEN SUKOHARJO - Aisyah Ammar Roxymawati; Mintasih Indriayu; Dewi Kusuma Wardani (STKIP Persada Khatulistiwa Sintang, 2026)
Vocational High Schools (SMK) are educational institutions that have a strategic role in producing competent, adaptive, and competitive graduates. However, the work readiness of students to enter the workforce remains a crucial issue. This study was conducted to (1) determine the effect of industrial work practices on work readiness and (2) determine the effect of learning facilities on work readiness of SMK students in Sukoharjo Regency. This study is a quantitative descriptive study. The study population was 176 grade XII SMK students majoring in Online Marketing Business. The research sample was 122 taken using the proportional random sampling method. Data collection through questionnaires was then analyzed using multiple linear regression using SPSS. The results of the study indicate that (1) there is an effect of industrial work practices on work readiness and (2) there is an effect of learning facilities on work readiness. It can be concluded that there is a partial or simultaneous influence between industrial work practices and learning facilities on student work readiness. These findings indicate the importance of improving the quality of the implementation of industrial work practices through more optimal collaboration with the business world and industry, especially in the field of marketing business. In addition, it serves as evaluation material for schools in providing adequate learning facilities.